(3OjhGf eMeO Hf YHOGddg Hf MeRIs - (3eMeO YHO Gddg Hf MeRI, CHhGdbGSes
(3ChdgG (B:s
(3bGd Ydjg GdSdGe aj jhe THGe, jeOM hGdOg(B: (3CgGLJc CWdGd YaJ hQShegG fYe hGdfhi de jfLM efgG SdjegG s
(3BNQgG (B:s
(3ef bUjOI bGdgG aj MQH THGe LhGHkG ef YdhGf Hf HTQ(B: (3CLdjJehge hbJdJe SQGJge hcGf ajge dOGYj GdNjQ eWdH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3fSNI JQLY ddbQf GdKGef JbOjQkGs
(3hGdhQbI GdChdi HNW oeZGjQs
(3hGfXQ OjhGf hGdOg YHOGddg Hf MeRIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B203 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs